As representações Cristãs e Greco-Romanas presentes no Inferno d’A Divina Comédia de Dante Alighieri - Borges, Géssica Maíra Nunes (2022)
Dante Alighieri was a italian poet born in Florence, in 1265. We don’t know in what moment he started to write his most famous work The Divine Comedy, but on 1327, Inferno was already known. This paper’s finality is to know the florentine poet history in order to undertand how he composed the Inferno, the most import part of The Divine Comedy. We seek to analyze how Alighieri used cristian and greek roman elemets to make his work. The main research sources were books from authors like Barbara Reyn- olds and Jayme Mason, papers and thesys, as well ilustrations from Gustave Dore. From that, concludes that this paper’s relevance is because we wil comprehend the inspirations of this author and how he knew how to use the already known sources e yet create his own piece, piece that pierced through centuries and became a historical heritage of world literature.